2010
DOI: 10.1007/s12664-010-0066-4
|View full text |Cite
|
Sign up to set email alerts
|

Population based study to assess prevalence and risk factors of gastroesophageal reflux disease in a high altitude area

Abstract: This population-based study in a high altitude area in India suggests a high prevalence (18.7%) of GERD. A younger age group, sedentary lifestyle, serum LDL >150 mg/dL, high consumption of meat, low consumption of salted tea and low consumption of fresh fruits were significant risk factors for development of GERD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 50 publications
4
41
0
1
Order By: Relevance
“…Prevalence rates have been estimated to be lower in Asia when compared to that of the western countries (<5% vs. 10% to 20%) [12]. The current articles on GERD in this Journal [13][14][15][16] demonstrate that contrary to previous belief, the prevalence of GERD in India is in fact much higher and similar to that reported in the Western countries. However, it is unclear if this represents a true increase in the prevalence or is the result of a better understanding of the disease symptoms, increased awareness of acid reflux, or the recent conduct of high quality epidemiological studies.…”
Section: Prevalence Of Gerd In Indiamentioning
confidence: 50%
“…Prevalence rates have been estimated to be lower in Asia when compared to that of the western countries (<5% vs. 10% to 20%) [12]. The current articles on GERD in this Journal [13][14][15][16] demonstrate that contrary to previous belief, the prevalence of GERD in India is in fact much higher and similar to that reported in the Western countries. However, it is unclear if this represents a true increase in the prevalence or is the result of a better understanding of the disease symptoms, increased awareness of acid reflux, or the recent conduct of high quality epidemiological studies.…”
Section: Prevalence Of Gerd In Indiamentioning
confidence: 50%
“…The sample size was calculated based on an anticipated prevalence of 18.7% [7], taking the confidence level of 95% and an absolute error of 1.5% and a non-response rate of 10% and using the formula:…”
Section: Methodsmentioning
confidence: 99%
“…This process was repeated till the required sample size was achieved. Each selected subject was interviewed with the aid of a valid questionnaire (in local language) containing items eliciting the demographic, lifestyle factors and the symptom score for GERD [7,8]. The scoring of symptoms was done on the basis of the frequency of symptoms both ranging from 0-3.…”
Section: Methodsmentioning
confidence: 99%
“…There are other questionnaire based cross-sectional studies by Sharma et al and Kumar et al, [9,10] which also showed a high weekly prevalence of GERD (16.2-18.7%).…”
Section: Introductionmentioning
confidence: 93%